MR Imaging of the Spine in Epidermal Nevus Syndrome - Booth, Timothy N.; Rollins, Nancy K. (American Journal of Neuroradiology, 2002)
Summary: We report two cases of epidermal nevus syndrome (ENS) involving the spine. MR imaging of the spine demonstrated intraspinal lipomas in both cases. Abnormal, enhancing, enlarged cervical and lumbosacral nerve roots were present in one patient. Spinal imaging for patients with ENS may help in the diagnosis of subtle intracranial manifestations, as it did in both of our cases. ENS has features similar to those of other neurocutaneous syndromes, such as neurofibromatosis type 1 and encephalocraniocutaneous lipomatosis.